2020
DOI: 10.1021/acs.macromol.0c01111
|View full text |Cite
|
Sign up to set email alerts
|

Can Self-Assembly Address the Permeability/Selectivity Trade-Offs in Polymer Membranes?

Abstract: In 1999, Freeman published a visionary article that proposed a molecular basis for the trade-off between permeability and selectivity for polymeric gas separation membranes, which is often codified as an “upper bound”. This work has had major impacts in the gas separation membrane community and is paralleled by developments in the water purification membrane literature. A common theme between both communities is optimizing free volume or pore size distributions in polymer membranes to maximize separation perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 81 publications
0
34
0
1
Order By: Relevance
“…This is a known trade-off in membrane science that is reflected in the formation of the upper bound line in a Robeson plot (permeability vs selectivity plot) . Up to now, the so-called isoporous membranes with relatively large free volume and very narrow pore size distribution have been shown to overcome the trade-off, demonstrating both high permeability and selectivity. , However, the challenging fabrication process and high cost of starting materials for these membranes preclude their broad industrial use. On the bright side, some novel polymer-based building blocks for constructing membranes are emerging to advance the selective transport of gases.…”
Section: Introductionmentioning
confidence: 99%
“…This is a known trade-off in membrane science that is reflected in the formation of the upper bound line in a Robeson plot (permeability vs selectivity plot) . Up to now, the so-called isoporous membranes with relatively large free volume and very narrow pore size distribution have been shown to overcome the trade-off, demonstrating both high permeability and selectivity. , However, the challenging fabrication process and high cost of starting materials for these membranes preclude their broad industrial use. On the bright side, some novel polymer-based building blocks for constructing membranes are emerging to advance the selective transport of gases.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, high selectivity can be achieved by having small pores with a narrow range of sizes. Therefore, there is usually a tradeoff between flux and selectivity (Judd and Jefferson, 2003;Park et al, 2017;Moon et al, 2020). In addition, there is generally an inverse relationship between membrane thickness (number of layers) and flux (Shirazi et al, 2014) which suggests a general trade-off between mechanical resistance and flux.…”
Section: Produced Water Treatmentmentioning
confidence: 99%
“…However, the increasing rigidity of molecular chains will stack molecular chains tightly, thus reducing permeability. A rather general tradeoff relation has been recognized between permeability and selectivity [ 13 , 14 ]. For PI membranes, we found that the high rigidity and large free volume structure in the membrane are conducive to good gas separation performance.…”
Section: Introductionmentioning
confidence: 99%